FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENGAMBILAN NILAI PEMBIAYAAN MURÂBAHAH - Rusydiana, Nina; Ali, A.M. Hasan (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2012)
In economic aspect, the existence of home industry gives substantial impact on the economy of a village. Tofu is one is potential household scale industries developed in Indonesia. In running their business, the producers also has disadvantages like the availability of sufficient capital to balanced the ability to repay the loan in accordance with its characteristics. One solution to solve this is by giving murâbahah finance. Reseach refeals that the factors that influence the decision value murâbahah financing to  producers are value of installments, number of installments, the amount of the worker and the capital value of the coefficient of determination value contribution is 0.705DOI: http://dx.doi.org/10.15408/aiq.v4i1.2533